The Maniacal Month of May 1998: A Historical Perspective on Pribumi and Tionghoa Conflict in Indonesia - Noel, Bret (Jurnal Sejarah dan Budaya, 2010)
May 1998 marks some of the most publicized accounts of violence against the ethnic Chinese minority in Indonesian history. It is important to notice that the word âpublicizedâ is used, because the riots during the month were not the most violent attacks on the Chinese community in Indonesia. Although hundreds of Indonesian Chinese businesses and homes were destroyed across the archipelago and many Indonesian Chinese were killed, what especially garnered global attention was the claim that hundreds of ethnic Chinese women and young girls were raped and brutalized during the riots. The claim that there had been widespread, racially-inspired rapes and the attention they have received is of historical consequence for Indonesia and more importantly for the native [pribumi], middle-class, Indonesians, who generally prefer to think that racism is a thing of the past. This time Indonesians were forced to recognize that ethnic violence is an Indonesian problem and not just an Indonesian Chinese problem.